Re-orienting transdisciplinary research and community-based participatory research for health equity. Issue 1 (4th February 2022) - Hohl, Sarah D.; Neuhouser, Marian L.; Thompson, Beti
Abstract: Introduction: Transdisciplinary (TD) research and community-based participatory research (CBPR) represent promising investigative approaches to ameliorate health disparities. Public investments in team-based TD research to address multifactorial public health problems have increased over the last two decades. Similarly, recognition that community participation in research and social action is essential to promoting health equity is reflected in increased prioritization of community engagement in research and practice. Yet, models that describe and guide the combined TD and CBPR approach are lacking. Methods: We utilized a qualitative, convergent parallel case study design that included document reviews and one-on-one interviews to assess how investigators from the Centers for Population Health and Health Disparities (CPHHD) initiative integrated TD team science and CBPR in their work, and what they perceived as the impact of that work on health equity. Results: Twenty-five CPHHD investigators and National Institutes of Health program staff participated in a one-on-one interview. Document and interview data informed the development of an iterative conceptual model of TD CBPR comprising five domains: problem focus, contexts, collaboration and partnership, outcomes, and societal impact of TD CBPR. Conclusions: TD team science and CBPR are integrally related; combining principles of both can facilitate more efficient, equitable progress toward team outcomes, improved population health, and increased health equity. This model could assist researchers and public health practitioners in designing community-relevant, scientifically rigorous research with practical implications for improving health and quality of life among marginalized populations.